Herpes zóster diseminado: caso clínico y revisión bibliográfica - Moya G., Nicolás; Neves J., Emilia (Revista Hospital Clínico Universidad de Chile, 2020)
Herpes zoster classical clinical presentation is the acute onset of multiple vesicles over an erythematous base, disposed over one or two dermatomes with up to 20 vesicles located outside the main dermatome. Disseminated herpes zoster is an atypical and rare form of presentation of herpes zoster, which manifests with lesions beyond the described territory. It occurs mainly in patients with some type of cellular immunosuppression. The diagnosis is made with the medical history and physical examination, however, it should be confirmed with laboratory tests. Treatment must be initiated early to avoid serious complications, such as bacterial infection of the lesions, post-herpetic neuralgia, or even central nervous system involvement. The drug of choice is intravenous acyclovir that must be maintained until the cessation of the appearance of new lesions, and then switch to its oral presentation for another 5-7 days. Disseminated herpes zoster mortality rounds 5-15%. There are varicella-zoster virus vaccines, that have been shown to reduce the incidence of herpes zoster relapses, however its utility to disseminated herpes zoster is uncertain and further studies are required. We present the case of a male patient with a history of rheumatoid arthritis who consults with multiple vesicles distributed throughout his body.